آليات ضمان الحقوق الثقافية للأقليات الدينية في الفقه الإسلامي والقانون العراقي - الزيداوي، قاسمية رويح سهيل; فيروزي، مهدي; البهادلي، أحمد حسن (جامعة الكوفة - كلية القانون, 2024)
إن الأقليات هم شريحة من شرائح كل مجتمع إنساني، تتمتع بحقوق وضمانات تكفلتها المعايير الإنسانية أن حقوق الأقليات الدينية والمذهبية في الأحوال الشخصية في العراق كدولة توجد فيه أقليات متنوعة وكثيرة؛ والدستور الإلهي (القرآن الكريم) الذي اعتبرهم جزءا من المجتمع البشري له حقوق وعليه واجبات ولا يجوز التفرقة بين أفراد المجتمع بأي حال من الأحوال، وإلى أن يجيء من يوحد الناس تحت نظام عالمي عادل سعت بعض الأنظمة أن تسن تشريعات وقوانين تهدف إلى جمع المجتمع الواحد بسلام ودون تفرقة. فالسؤال الأصلي لهذه الدراسة هي ما هي حقوق الثقافية للأقليات الدينية وما هي آليات تضمينها في الفقه الإسلامي والقانون العراقي كما لا ينص القانون العراقي بشكل كاف على حماية حقوق الأقليات الدينية الثقافية، مما يعرضها للانتهاكات. وتفتقر بعض الاتفاقيات الدولية المتعلقة بحقوق الإنسان إلى نصوص محددة لحماية حقوق الأقليات الدينية الثقافية، أو قد تتضمن نصوصا قابلة للتأويل. كما تفتقر الدول إلى آليات فعالة لتنفيذ القوانين والاتفاقيات المتعلقة بحقوق الأقليات الدينية الثقافية. Minorities are a segment of every human society, enjoying rights and guarantees guaranteed by humanitarian standards. The rights of religious and sectarian minorities in personal status in Iraq as a state in which there are diverse and numerous minorities; and the divine constitution (the Holy Quran) which considered them part of human society has rights and duties and it is not permissible to differentiate between members of society in any way, and until someone comes to unite people under a just global system, some regimes have sought to enact legislation and laws aimed at bringing together one society in peace and without discrimination. The original question of this study is what are the cultural rights of religious minorities and what are the mechanisms for including them in Islamic jurisprudence and Iraqi law Iraqi law does not adequately provide for the protection of the cultural rights of religious minorities, which exposes them to violations. Some international human rights agreements lack specific provisions to protect the rights of religious and cultural minorities, or may include provisions that are open to interpretation. Countries also lack effective mechanisms to implement laws and agreements related to the rights of religious and cultural minorities.
Keywords: حرية المعتقدات الدينية -- الأقليات المذهبية -- الفقه الإسلامي -- التشريعات العراقية